RENAL DENERVATION: IMPACT OF ANATOMY ON PROCEDURE OUTCOME - TATIANA Y. Chichkova; SERGEY E. Mamchur; MARIA P. Romanova; EGOR A. Khomenko; ALEXANDR Y. Ivanov (Фундаментальная и клиническая медицина, 2018)
Aim. To evaluate early and long-term results of renal denervation in patients with resistant arterial hypertension and different anatomy of renal arter-ies as compared to those who underwent a conser-vative treatment.Materials and Methods. We recruited 53 con-secutive patients with resistant hypertension (25 males and 28 females, median age 54 (interquartile range 43-66) years). Depending on the anatomy of renal arteries defined by non-invasive visualization, patients who underwent renal denervation were as-signed into the subgroups with typical anatomy (A1 and A2) and with multiple arteries (B1 and B2). Pa-tients with complex renal anatomy unacceptable for the surgery or those who refused to undergo renal denervation received conservative therapy. Evalua-tion of blood pressure (BP) was performed at the baseline and upon 12 months of follow-up.Results. Patients with typical anatomy of renal arteries were characterized by significant decrease in mean BP as well as its variability (from 20 to 11 mmHg and from 17 to 10 mmHg for systolic and diastolic BP, respectively). Index of BP time de-creased from 100 to 25% for systolic BP and from 90 to 45% for diastolic BP (р < 0.05). Similar dy-namics were revealed in the B1 subgroup (all arter-ies available for ablation) of patients with multiple arteries. In the B2 subgroup (≥ 1 artery unavail-able for ablation) office and 24-hour BP decreased significantly from 165/95 to 155/90 mmHg (р ≤ 0.05), and mean systolic BP also decreased from 165 to 150 mmHg (p = 0.04). Patients with com-plete renal denervation (A1 + B1) were character-ized by a significant reduction of mean systolic BP (25 mmHg) as compared to those with incomplete renal denervation (10 mmHg) or conservative therapy (1 mmHg).Conclusions. The long-term efficacy of renal denervation was superior to conservative therapy in BP reduction, its variability and time index re-gardless of the anatomy of renal arteries. However, BP reduction in patients with incomplete denervation was less pronounced.